2022
DOI: 10.1088/1755-1315/1078/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Cards for Circularity (CFC): Reflections on the use of a card-based circular design tool in design education

Abstract: The transition to a Circular Economy (CE) requires designers to, more than ever, concurrently develop a circular design, supply chain and business model, and anticipate how products and buildings function over time. To address these challenges, recent studies identified specific knowledge and competencies for designers. However, it remains unknown to what extent future designers (students) are prepared to address the CE in design practice. Therefore, this study investigates how architecture students currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, a recent literature review on ECE found institutions are still slow to adopt it as a fundamental part of the curriculum [11]. Specifically, in the field of architectural design, there is even less information addressing education from a CE perspective, with only a couple of published cases [12], [13]. Therefore, there is a significant knowledge gap regarding architectural design education in the context of circularity.…”
Section: Introduction 678mentioning
confidence: 99%
“…However, a recent literature review on ECE found institutions are still slow to adopt it as a fundamental part of the curriculum [11]. Specifically, in the field of architectural design, there is even less information addressing education from a CE perspective, with only a couple of published cases [12], [13]. Therefore, there is a significant knowledge gap regarding architectural design education in the context of circularity.…”
Section: Introduction 678mentioning
confidence: 99%